Note from the editor: Climate change - what economic sociology has to offer - Anita Engels (economic sociology_the european electronic newsletter, 2020)
Welcome to crisis mode. Anthropogenic climate change is not only globally recognized as a well-established scientific analysis of what is currently happening to planet Earth, but it even seems to be accelerating recently. While governments are trying to contain the Covid-19 pandemic and struggle with its dramatic short- and long-term effects, the global climate crisis is building in the background with maybe even more far-reaching consequences.
Keywords: 300